Archaeology of Mind in the Hebrew Bible/Archäologie alttestamentlichen Denkens = Archäologie alttestamentlichen Denkens - Wagner, Andreas 1963-; Oorschot, Jürgen van 1957-; Allolio-Näcke, Lars 1975-; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2023)
Research into the Hebrew Bible, Ancient Near East, Philosophy and History have long considered whether thought in the cultural area of the ancient Middle East differs from that in the western Mediterranean. The inclusion of neurobiology, psychology, brain research and evolutionary research will widen this horizon and allow new approaches. This volume provides in depth insides into this Archaeology of Mind in 22 contributions
Seit langem befassen sich alttestamentliche Exegese, Altorientalistik, Philosophie und Geschichte mit der Frage, ob sich das Denken im Kulturraum des Alten Orients, Ägyptens, Syrien/Kanaans und Israel/Palästinas vom westlichen Mittelmeerraum unterscheidet. Die Einbeziehung von Neurobiologie, Psychologie, Hirn- und Evolutionsforschung ermöglicht neue Ansätze. Die Beiträge dieses Bandes geben einen Einblick in diese Archäologie des Denkens
In English
Keywords: RELIGION / Psychology of Religion; Aspective; Western thought; cognition; evolution of the brain; Konferenzschrift -- 2018